SYSTEMATIC LITERATURE REVIEW ON SUSTAINABLE CITIES AND COMMUNITIES: THE ROLE OF ECO-TOURISM INDUSTRY, CREATIVITY AND INNOVATION, AND INFRASTRUCTURE INVESTMENT - Mulia Rahmah; Arissetyanto Nugroho; Darmansyah, Darmansyah (International Journal of Social Science, 2025)
The Sustainable Development Goals (SDGs) are a global agreement aimed at improving the well-being of society. This study uses a systematic literature review approach to analyze the aspects of Sustainable Cities and Communities, specifically focusing on the role of the ecotourism industry, creativity and innovation, and infrastructure investment. The research findings reveal four main topics identified based on the journals reviewed. Several factors that play a significant role in achieving the SDGs include innovation, infrastructure investment, environmental governance, education, and the development of ecotourism.